(untitled) (Research, Society and Development, 2021)
Football is the most popular sport in the world and involves the availability of information of footballers and teams to investigate success in this sport. In account of these aspects, the current study aims to analyze the influence of ball possession time, passes and shots on target in winning Premier League football matches. The methodology adopted consists of a quantitative, descriptive and documentary research, in which the sample is represented by all the 380 Premier League (PL) matches of the 2015/2016 season. The analysis process was made by the use of the association technique, present in the data mining process, with the support of the Weka software. The results suggest that shots on target, as well as its interaction with ball possession and passes - total passes, accuracy of passes, accuracy of passes inside the opponent’s field and long passes - influenced the final result of the match. Based on the results, the conclusion is that direct play alternatives, such as presenting less ball possession time and more long passes, associated with more shots on target, showed to be more beneficial for football clubs to win football matches.